Comparative study of a liposome and emulsion system with cinnamon essential oil on the quality and proteolysis of refrigerated minced pork - Wu, Kegang; Zhang, Tong; Chai, Xianghua; Wang, Pingping; Duan, Xuejuan (Frontiers in Nutrition, 2024)
Essential oils have been recognized for their strong antibacterial property, making them an innovative approach for meat preservation. However, their chemical instability and direct impact on meat protein limit their application. To overcome these limitations, various loading systems have been explored. This study aimed to compare the effect of cinnamon essential oil (CEO) loaded in liposome and emulsion system on the proteolysis of minced pork, and to evaluate the advantages of each delivery system in prevent microorganism-induce quality deterioration of meat. Minced pork treated with CEO-liposome exhibited lower pH, TVB-N, and TVC values than CEO-emulsion, and better protection against microorganisms. SDS-PAGE analysis confirmed that CEO-liposome was more effective to protected proteins from degradation. Moreover, CEO-liposome produced less bitter amino acids and harmful biogenic amines. Antibacterial mechanism indicated that CEO-liposome exhibited stronger inhibitory effect against major spoilage bacteria in meat products through increasing cell membrane permeability. Membrane damage were further supported by an increase in conductivity and the leakage of nucleic acid. Compared to emulsion system, CEO-liposome emerged as the effective preservative for minced pork preservation. These results provided important theoretical support for using bio-active compound delivery system to prevent meat from the microorganism-induced quality deterioration.